Sideband-controllable soliton pulse with bismuth-based erbium-doped fiber - Tan, Sin Jin; Tiu, Zian Cheak; Harun, Sulaiman Wadi; Ahmad, Harith (Optical Society of America, 2015)
A sideband-controllable soliton mode-locked erbium-doped fiber laser is successfully demonstrated utilizing the nonlinear polarization rotation technique. The sidebands can be produced or suppressed by performing simple polarization light tuning with a polarization controller. It is believed that the elimination of the sidebands is due to the dispersive waves that are filtered out by the polarization-dependent isolator in the resonator. With the elimination of the Kelly sidebands, the obtained 3 dB bandwidth is 10.6 nm and the attainable pulse duration is 0.86 ps. In this experiment, it is proven that the existence of Kelly sidebands limits the attainable pulse duration.